The National Holocaust Museum and the Hollandsche Schouwburg : observe, reflect, act - Gringold, Annemiek 2024- Herausgeber; Waterman, Asjer, 1992- 1992- Herausgeber; Nationaal Holocaust Museum (Waanders Publishers, 2024)
The National Holocaust Museum tells the story of the Nazi persecution and murder of the Jews of the Netherlands. Before the Second World War, Jews and non-Jews lived side by side. They had the same rights. But during the war, the Nazis and their collaborators killed around six million Jews in Europe. That was the Holocaust or Shoah. This is the first and only museum to relate the history of the persecution of the Jews of the entire Netherlands. Including the day-to-day life of Jews on the eve of the Second World War, the liberation as Jews experienced it, and how the Holocaust has been treated in our national culture of remembrance: all this is examined in the museum and this book. Once a theatre, the Hollandsche Schouwburg was seized by the Nazis in the Second World War. From July 1942, Jews ordered to report for deportation were assembled here. Tens of thousands of people passed through these doors. Many spent hours, days, even weeks locked in here before being sent to concentration and extermination camps. Today, it?s a memorial for all the victims of the Holocaust. 00Exhibition: opening of the Holocaust Museum, Amsterdam, The Netherlands (10.03.2024)